2020
DOI: 10.3389/fncel.2019.00581
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Self-administration and Extinction Inversely Alter Neuron to Glia Exosomal Dynamics in the Nucleus Accumbens

Abstract: Alteration of glutamatergic synaptic plasticity in the Nucleus Accumbens (NAc) has been implicated in cocaine-seeking behaviors. Astroglial mechanisms for maintaining extracellular glutamate homeostasis through cysteine/glutamate exchanger (xCT) and glutamate transporter GLT1 are dysregulated following cocaine exposure and contribute to altered glutamatergic synaptic plasticity. However, how these astroglial proteins become dysregulated in cocaine addiction remains unknown. We recently showed that neuron to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Cocaine enhances dopaminergic synaptic transmission by blockade of the dopamine transporter (DAT), which in turn leads to elevation of extracellular dopamine levels in the nucleus accumbens [31]. In our previous study, it was also shown that cocaine self-administration elevated extracellular accumbal dopamine levels during last cocaine session, whereas it did not affect basal accumbal dopamine levels [20].…”
Section: Discussionmentioning
confidence: 96%
“…Cocaine enhances dopaminergic synaptic transmission by blockade of the dopamine transporter (DAT), which in turn leads to elevation of extracellular dopamine levels in the nucleus accumbens [31]. In our previous study, it was also shown that cocaine self-administration elevated extracellular accumbal dopamine levels during last cocaine session, whereas it did not affect basal accumbal dopamine levels [20].…”
Section: Discussionmentioning
confidence: 96%
“…Cocaine induced EV regulation involves the sigma 1 receptor (Sig-1R), ADP ribosylation factor 6 (ARF6) and myosin light chain kinase ( Machado-Pineda et al, 2018 ) but still remains poorly understood. Cocaine self-administration was shown to alter the signaling of neuronal exosomes to astrocytes using a CD63 reporter ( Jarvis et al, 2019 ). However, no studies have investigated the role of cocaine on extracellular vesicular proteins in human microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding their role in HIV-1-induced aging will be an important area of research that warrants investigation. It has been reported that cocaine self-administration in mice reduced uptake of NDEVs by the astrocytes primarily in the motor cortex, an effect that was effectively reversed by extinction training [ 205 ]. Drugs of abuse like cocaine, morphine, methamphetamine [ 206 , 207 , 208 ] can induce chronic low-level inflammation and can also potentiate inflammatory status in the context of HIV-1 [ 209 , 210 , 211 ], which together can contribute to the process of inflammaging.…”
Section: Role Of Neurons—inflammasomes and Agingmentioning
confidence: 99%